Antonia Pozzi e la poesia del corpo - Bernabò, Graziella (Dialogoi. Rivista di studi comparatistici, 2020)
Antonia Pozzi’s poetry - literally elaborate, but warm and corporeal - remained misunderstood in the Thirties, because it was far from the disciplined and sober literary taste of his intellectual environment: the philosopher Antonio Banfi’s group. Only today that the poetry of the body and desire has attracted attention on an international level of the public and critics it is possible to appreciate it in all its surprising thematic and stylistic originality.